2020
DOI: 10.1038/s41598-020-67540-2
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear optical induced lattice in atomic configurations

Abstract: Traditional artificial lattice with untunable refractive index have been restricted to flexible applied to kinds of micro medium imaging. This study proposes a novel approach to quantifying lattice using nonlinear optically induced periodic lattice, which possesses a striking feature of tunable refractive index, to further broaden current knowledge of optical imaging equipment. We conduct self-dressed and dual-dressed nonlinear four-wave mixing (FWM) signal modulation in the atoms by using the dressing effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…And the method showed that a type conversion is realized from amplitude electromagnetically induced optical lattices to synthesized electromagnetically induced optical lattices by adding a detuning term. [111] As a reconfigurable optical platform, electromagnetically induced optical lattices have great potential for DTP research in time domain.…”
Section: Photonic Crystals and Latticesmentioning
confidence: 99%
See 1 more Smart Citation
“…And the method showed that a type conversion is realized from amplitude electromagnetically induced optical lattices to synthesized electromagnetically induced optical lattices by adding a detuning term. [111] As a reconfigurable optical platform, electromagnetically induced optical lattices have great potential for DTP research in time domain.…”
Section: Photonic Crystals and Latticesmentioning
confidence: 99%
“…(e) The optical lattice is constructed by nonlinear effect. This method showed that a type conversion is realized from amplitude electromagnetically induced optical lattices to synthesized electromagnetically induced optical lattices by adding a detuning term [111]. (f) Spatiotemporal intensity profiles emerging in the course of modulational instability development in the mode-locked lasers [112].…”
mentioning
confidence: 99%